Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Mesure 2 : Programme de maintien en poste : Volets Réseaux communautaires et Maisons d’enseignement : Prospectus 2014-2018 - Dialogue McGill (2014)
Le Projet de formation et de maintien en poste des professionnels de la santé de l’Université McGill contribue aux initiatives du Québec destinées à assurer aux Québécois d’expression anglaise l’accès dans leur langue à la gamme complète de services de santé et de services sociaux, et ce, au moyen de diverses mesures visant à fournir et à maintenir en poste un complément de main-d’œuvre suffisant, capable d’offrir des services en anglais. Le projet constitue un outil additionnel favorisant l’application et la bonification des programmes régionaux d’accès aux services de santé et aux services sociaux en langue anglaise, conformément à la Loi sur les services de santé et les services sociaux. Ce Projet a pour objectifs précis de susciter des initiatives de formation et de maintien en poste qui fourniront aux professionnels de la santé et des services sociaux l’occasion d’améliorer leur capacité d’offrir des services en anglais, ainsi que l’occasion de travailler là où ils seront en mesure de répondre aux besoins des populations d’expression anglaise du Québec. Le Projet vise également à promouvoir la recherche et le partage de l’information quant aux approches visant à réduire les barrières en matière d’accès aux services de santé et aux services sociaux pour les Québécois d’expression anglaise.

Letter of Support for QCGN - Zucchi, John (2014)

[Letter re: Bill 10 - Letters of Support of QCGN] - Committee for Anglophone Social Action (CASA); Coasters Association; Community Health and Social Services Network (CHSSN); Jeffery Hale - Saint Brigid's (JHSB); Neighbours Regional Association of Rouyn-Noranda; Quebec Community Groups Network (QCGN); Quebec Federation of Home and School Associations (QFHSA) (2014)

[Letter Regarding Bill 10 from QCGN President] - DePoe, Lawrence (2014)

Mémoire du Quebec Community Groups Network déposé à la Commission de la santé et des services sociaux de l’Assemblée nationale du Québec : Le projet de loi n° 10, loi visant à modifier l’organisation et la gouvernance du réseau de la santé et des services sociaux, notamment par l’abolition des agences régionales - Quebec Community Groups Network (QCGN) (2014)

Retention Program for the McGill University Training and Retention of Health Professionals Project : Evaluation of the retention program measure and recommendations - Gagnon, Marie-Pierre (Dialogue McGill, 2014)
This report presents an evaluation of the activities implemented under the Retention Program, in relation to the Support for Health and Social Services Institutions and Support for Educational Institutions in order to highlight the main strengths and areas for improvement. The mandate was to identify strategies that could help to increase the impact of the internship program on the retention of health and social services professionals in the health and social services network. The evaluation would then contribute to the ongoing improvement of this program, by providing some direction to guide the actions of those responsible for the McGill University Training and Retention of Health Professionals Project and project partners.

Long Live Healthy Development Framework - Buffitt, Kimberly (2014)
Keywords: Official Language Minority Community (OLMC)

Recovery Support Program : A Community Wellness Program for English-speaking People with Mental Illness - Jeffery Hale - Saint Brigid's (JHSB) (2014)

Brief Submitted to La commission de la santé et des services sociaux de l'Assemblée nationale du Québec Concerning Bill 10, An Act to Modify the Organization of the Health and Social Services Network, in Particular by Abolishing the Regional Agencies - Quebec Community Groups Network (QCGN) (2014)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)